Leading names in education: Andrés Manjón y Manjón and Escuelas del Ave María. (Journal of Parents and Teachers, 2012)
Andrés Manjón is the creator of the wide network of Ave María schools and formative centres for teachers. In his educational work was shown a combination between theory and practice in order to achieve a good formation of the students in the workplace. He defended learning through active classes where the students can participate and become a protagonist in the teaching-learning process. Of Catholic ideology, he was opposed to traditional pedagogy and he stimulated progressive learning. In the late nineteenth century he became professor of canon law faculty at Granada’s university.
Keywords: Leading names in education; Andrés Manjón; Ave María schools; education; learning; active learning